2011
DOI: 10.1348/026151010x523040
|View full text |Cite
|
Sign up to set email alerts
|

Comprehension and production of body part labels in 2‐ to 3‐year‐old children

Abstract: This study examined which body part labels children could (i) produce when the experimenter touched different locations on her own body, asking each time 'What's this?' and (ii) comprehend by touching the correct locations on their own bodies in response to the experimenter asking 'Where's the [body-part label]?'. Seventeen children aged between 26 and 41 months, tested in a repeated measures procedure, were presented with 50 different body part stimuli in 200 test trials per child. Overall, the children produ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
27
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 37 publications
(61 reference statements)
2
27
0
Order By: Relevance
“…A similar advantage for head features over body parts has also been reported in verbal tasks. It was shown that the comprehension and production of body part labels in 2-to 3-year-old children was more efficient for body parts located on the face than on the body (Camões-Costa et al, 2011). In the present study, we found that this precedence in body knowledge development for facial parts relative to other body parts persists in older children (5-to 11-year-olds).…”
Section: Spatial Representation Of Face and Body Partssupporting
confidence: 57%
See 2 more Smart Citations
“…A similar advantage for head features over body parts has also been reported in verbal tasks. It was shown that the comprehension and production of body part labels in 2-to 3-year-old children was more efficient for body parts located on the face than on the body (Camões-Costa et al, 2011). In the present study, we found that this precedence in body knowledge development for facial parts relative to other body parts persists in older children (5-to 11-year-olds).…”
Section: Spatial Representation Of Face and Body Partssupporting
confidence: 57%
“…The development of the ability to label body parts is highly related to the topographical body representation (Camões-Costa, Erjavec, & Horne, 2011;Witt, Cermak, & Coster, 1990). For example, Camões-Costa et al (2011) asked English-speaking children aged from 2 to 3 years 5 months old to label each body part pointed at on experimenter's body. They observed that children named head features more accurately than joints (e.g., elbow, knee, ankle) or broad body parts (e.g., bottom, belly, head).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…During its first years, a child develops its own body scheme, a coherent sense of its body and beliefs concerning body image which are then used to describe one's appearance (Camões-Costa, Erjavec & Horne, 2011). The relationship with carers and parental attitudes towards their child's looks start to outline the way the child values itself (Brownell, Zerwas & Ramani, 2007).…”
Section: Introductionmentioning
confidence: 99%
“…After the period of reaching puberty and then adulthood, when it falls quite deeply due to external opinions (Bucchianeri et al, 2013), it gradually increases during middle adulthood (Kochan-Wójcik & Piskorz, 2010), and on the threshold of old age it plummets as a result of confrontation with the evident signs of aging and the general, often negative opinions about old age (Ferraro et al, 2008). Not only does body image evolve with age (Tiggemann, 2004;Lipowska & Lipow ski, 2006b;Camões-Costa et al, 2011), but it can also be disrupted at any stage of experiencing one's body, which contributes, among other things, to eating disorders or body dysmorphic disorder, both in women and in men (Brytek-Matera, 2012;Hrabosky et al, 2009;Schuster, Negy & Tantleff-Dunn, 2013).…”
Section: Introductionmentioning
confidence: 99%